PENYELESAIAN SENGKETA HAK ATAS TANAH MASYARAKAT HUKUM ADAT - Adonia Ivonne Laturette (Faculty of Law, Universitas Pattimura, 2016)
Settlement of Disputes over customary law community land is through deliberations to reach consensus with mutual respect for the position of each party which also involves the Regional Government. If the business through consultation does not reach an agreement then the settlement of the dispute must be settled through legal channels through the State Administrative Court with the initial mechanism that the customary law community encourages the Official of the Land Office to issue the customary land status of customary law community. Based on a Decree issued by the Land Office Officials may be used as a suit to the State Administrative Court.